(untitled) (ASEAN Engineering Journal, 2019)
Construction materials are selected based on two factors: structural integrity and economy. However, there is an emerging issue with regards to building materials, and that is sustainability, which considers the environmental load of a construction material. Bamboo’s lightweight and flexibility make it a good alternative for residential construction in seismic. In this study, bamboo was tested for its material properties. Layered tensile tests and full-culm compressive tests were done to get the material properties of the bamboo. The top part of the bamboo culm recorded the highest tensile strength per layer, with its outer layers having tensile strength as high as 600 MPa. The tensile strength of its middle and inner layers, on the other hand, were approximately 450 MPa and 180 MPa, respectively. As for the compressive strength, the top part of the bamboo culm recorded the highest compressive strength with an average of 76.84 MPa. The middle part of the bamboo culm recorded the lowest compressive strength with an average of 62.55 MPa. The bottom part of the bamboo culm recorded an average compressive strength of 69.49 MPa. These properties were then used to construct an orthotropic material model and simulate the stresses using finite element modeling. The FEM model of a simply-supported beam with a concentrated load at midspan was made. To validate the orthotropic material model for bamboo, three-point bending tests of bamboo beams were conducted and compared with the simulation results. The results show that in modeling the material properties of the bamboo to check for deflections, the orthotropic model gives more accurate results.